2020
DOI: 10.9734/irjpac/2020/v21i2430372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment and Gamma Irradiation on Protein of Selected Millet Grains

Abstract: The present investigation was conducted to find out the effects of heat or irradiation combined on protein. Sorghum, pearl millet, foxtail millet were used in the study. Whole (WC) and dehulled (DC) grains were treated either with heat (170°C) or irradiation at 1.0 kGy / 2.5 kGy and stored for 90 days. There was a significant (p<0.05) effect of treatments, storage and grain and their interactions on protein. The mean protein was 9.89 percent and there was a reduction in protein content of the grains due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Food irradiation or food infrared radiation technology is the application of ionizing radiation to food which helps enhance the shelf life of the food by inactivating microorganisms and ensures the food safety and inviolability (Zhang et al, 2018;Sujatha et al, 2020). Irradiation is used for sterilization of food products, increasing their shelf life (Shalaby et al, 2016).…”
Section: Irradiation/infrared Radiationmentioning
confidence: 99%
“…Food irradiation or food infrared radiation technology is the application of ionizing radiation to food which helps enhance the shelf life of the food by inactivating microorganisms and ensures the food safety and inviolability (Zhang et al, 2018;Sujatha et al, 2020). Irradiation is used for sterilization of food products, increasing their shelf life (Shalaby et al, 2016).…”
Section: Irradiation/infrared Radiationmentioning
confidence: 99%
“…Sujatha et al (2020) reported that the protein structure of whole and dehulled grains of sorghum, pearl millet, and foxtail millet changed due to cleavage of disulfide bonds on gamma irradiation along with improvement in protein content (9.1%-11.3%). Sujatha et al (2018) reported that irradiation of pearl millet using 60 Coγ source with two doses 1.0 and 2.5 kGy improved the in vitro digestibility of pearl millet starch (71.70%-77.89%).…”
Section: Irradiationmentioning
confidence: 99%
“…In addition, Falade and Kolawole (2013) stated that oil absorption capacity (OAC) of millet flour can be affected at high absorbed doses of gamma irradiation since OAC is dependent on the capability of oil entrapment in the non‐polar side chains of proteins. Sujatha et al (2020) reported that the protein structure of whole and dehulled grains of sorghum, pearl millet, and foxtail millet changed due to cleavage of disulfide bonds on gamma irradiation along with improvement in protein content (9.1%–11.3%). Sujatha et al (2018) reported that irradiation of pearl millet using 60 Coγ source with two doses 1.0 and 2.5 kGy improved the in vitro digestibility of pearl millet starch (71.70%–77.89%).…”
Section: Novel/advanced Techniquesmentioning
confidence: 99%